Surface Electrical Stimulation for Persistent Stuttering and Concomitant Orofacial Disorders: A Multiple Case Study. Issue 4 (August 2020) - Merlo, Sandra
This multiple case study analysis describes the immediate effects on speech fluency of transcutaneous electrical nerve stimulation (TENS) applied to participants with persistent stuttering and concomitant orofacial disorders. Study participants were 14 adolescents and adults who stuttered and had jaw clenching bruxism or mouth breathing. Participants experienced low-frequency TENS applied at mild motor level for 20 minutes with electrodes placed at the lower third of the face (Area A), submandibular region (Area B), posterior neck (Area C), or shoulder girdle (Area D), with speech fluency assessed immediately before and after each stimulation.For participants with stuttering and bruxism, AB stimulation reduced the median frequency of syllables stuttered by 27% and reduced the median duration of the three highest stuttering moments by 29%. In addition, for participants with stuttering and mouth breathing, CD stimulation reduced the median duration of the three highest stuttering moments by 28% and increased their median speech rate by 113%. As a single session of TENS may help participants with stuttering and concomitant orofacial disorders better use fluency shaping techniques, the therapeutic potential of TENS for treating stuttering should be further investigated.